2014
DOI: 10.1128/jcm.01701-13
|View full text |Cite
|
Sign up to set email alerts
|

Toxin-Producing Clostridium difficile Strains as Long-Term Gut Colonizers in Healthy Infants

Abstract: c Clostridium difficile is a colonizer of the human gut, and toxin-producing strains may cause diarrhea if the infectious burden is heavy. Infants are more frequently colonized than adults, but they rarely develop C. difficile disease. It is not known whether strains of C. difficile differ in the capacity to colonize and persist in the human gut microbiota. Here, we strain typed isolates of C. difficile that had colonized 42 healthy infants followed from birth to >12 months of age by using PCR ribotyping of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 41 publications
7
51
2
3
Order By: Relevance
“…Figure 3 summarizes the longitudinal changes of C. difficile bacteria in the 18 toxigenic C. difficile-positive infants. In agreement with findings of previous studies (12,23), specific single strains of the same genotype were retained over time in each of the 11 infants who yielded toxigenic C. difficile isolates on at least two occasions. These results suggested that C. difficile in a majority of infants was not transient, but rather was a colonizer, in their intestines.…”
Section: Table 4 Isolation and Characterization Of Toxigenic Clostridsupporting
confidence: 80%
See 4 more Smart Citations
“…Figure 3 summarizes the longitudinal changes of C. difficile bacteria in the 18 toxigenic C. difficile-positive infants. In agreement with findings of previous studies (12,23), specific single strains of the same genotype were retained over time in each of the 11 infants who yielded toxigenic C. difficile isolates on at least two occasions. These results suggested that C. difficile in a majority of infants was not transient, but rather was a colonizer, in their intestines.…”
Section: Table 4 Isolation and Characterization Of Toxigenic Clostridsupporting
confidence: 80%
“…It is probable that PR 014 is the most common strain type, not only in healthy infants but also in adult CDI patients, in Belgium, and this may support the recently proposed hypothesis that asymptomatic infants are a reservoir of pathogenic strains and contribute to the mediation of CDI in adults (12,14,23). The results of a literature search support the associations of specific PRs between infants and adult patients in other countries, namely, PR 014 in France (12,38) and PR 001 in Sweden (23,39).…”
Section: Fig 3 Longitudinal Changes In Bacterial Counts and Genotypessupporting
confidence: 60%
See 3 more Smart Citations